The Effects of Endurance and Resistance Training on Systemic Inflammatory Markers and Metabolic Syndrome Parameters in Overweight and Obese Men - Khalid Mohamadzadeh Salamat; Nuredin Bakhtiari (Islamic Azad University, 2017)
Introduction: The purpose of this study was to investigate the effects of endurance and resistance training on systemic inflammatory markers and metabolic syndrome parameters in overweight and obese men. Methods: 33 volunteer participants (BMI=27.39 kg/m2) were randomly divided into three groups (n=11), namely, an endurance training (ET) group, a resistance training (RT) group, and a control group. The ET and RT groups trained for eight weeks at three sessions a week and 150 min per week. Before the training and 72 hours after the last exercise session, blood samples were collected from the subjects for assays on interleukin-1β (IL-1β), IL-6, tumor necrosis factor-α (TNF-α), adiponectin, intracellular adhesion molecule-1 (ICAM-1), high-sensitivity C-reactive protein (hs-CRP), glucose, insulin, and blood lipids and lipoproteins. The percentage body fat, waist circumference, WHR, and blood pressure of the subjects were also measured before and after the training protocols. Analysis of variance (ANOVA) with repeated measures test and significant level of 0.05 was used for all statistical analysis. Results: After training, the ET and RT groups showed a significant decrease in hs-CRP, percentage body fat, insulin and insulin resistance index, triglycerides, and total cholesterol (P<0.05). Both groups likewise showed a significant increase in adiponectin (P<0.05). Only the changes in LDL-C and TNF-α were significant between the ET and RT groups (P<0.05). Conclusion: In general, the effects of resistance training on some of the systemic inflammatory markers and metabolic syndrome parameters of the overweight and obese men were incomparable to those of endurance training.